Tempos misteriosos: uma história da população rural pelas estradas do mundo moderno (Paraíba, 1932-1962) - Burity, Luiz Mário Dantas (2017)
The mysterious hinterlands made the imagination and the quotidian of the people who have lived in their frontiers. The delighted creatures, with the greatest courage and force, impossible for the humans, have been habited there, between the thorns of the vegetation and the wilderness of the plains. During the period started with the dry of 1932 and finished with the murder of the peasant leader João Pedro Teixeira in 1962, the rural workers met the new time, which turn their universe. The objective of this paper was discourse how agrarian people lived the modernization of the rural world. The modernization was composed with the projects of renovation, expansion, democratization and emancipation, like Néstor Canclini (2000[1989]) said. It happens in the same time of the processes of rationalization, read disenchantment of the world, to cite Max Weber (2004[1920]) and Antônio Pierucci (2005[2003]), of the growing of the futurist regime of historicity, according with Reinhart Koselleck (2006[2003]) and François Hartog (2014[2003]), of enlargement of the public sphere, in the way of Jürgen Habermas (2014[1962]). The change was made with the games of powers, in the middle of which appears the concept of reaction. This concept opened itself for the possible behaviors and representations in the scenario where the changes were happening. It talks about the values, the habits, the traditions of that people, but with the conflicts which involves the default partially shared for them, according with Edward Thompson (2011[1963]) and Roger Chartier (2002[1985]). Those reactions appears in the middle of the territories which involves the different historic cultures that was been playing, like Elio Chaves Flores (2007) said. The documentation was composed of the criminal and civil processes press in the Revista do Foro; of the agricultural supplements of the newspaper A União; of the magazine Parahyba-Agrícola; of the brochures; of the regionalist romances; and with the reports, laws, and another references with the punctual use. This research had assumed the topic that didn’t existe ignorance in the streets where the peasants walks in the politics world, that population bargain all the time the ways of that process, doing a political culture with their traditions and the references of the new time. The search shows the different lectures that the rural population did and like they movement themselves with those. This world occupied for politics bosses, banditries and clerics was dividing places with the public power. With this, the life of those characters changed a lot, they lost power and walked in a rational way. But the modern institutions also made a diagnosis of those changes, reading they like a homogeny group in the same category and smaller than the others. The construction of the modern calendar was involved for the representations fights, which changed the ways during the moment when the projects arrived in the quotidian of the rural population. So, the agriculture press was an important support for the rationalization of those questions and for the constructions of them like a public topic. Thus, the experiences of the cattle breeders, cotton and sugar cane growers show the symbolic violence and the conflicts which made this process. During this time, the peasants won, time after time, a bigger space in the public world, growing the agrarian question in the first position of the national themes and bargain, inside and outside the institutional ways, another forms to live the modern world. For that, the little properties, sometimes, construct fences around the land and the livers expulsed of the mills bargain the payment for their investments. With this, the different curves of the migrations and the growing of the demographic numbers proves how was wrong to discourse about rural exodus, the agrarian reform transform itself in a project into the legislative houses of the country and the peasant leagues show the movements of the rural population with the instruments of the modern, in the opposite way than the bigger properties did. In other words, the modernization was an important scenario for the democratization, which didn’t walk in a regular street, but in the middle of a lot of run overs and new routes, at least until 1964, when the civil-military coup let that process over.